2011
DOI: 10.1016/j.expneurol.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones influence corticotropin releasing factor receptor colocalization with delta opioid receptors in CA1 pyramidal cell dendrites

Abstract: Stress interacts with addictive processes to increase drug use, drug seeking, and relapse. The hippocampal formation (HF) is an important site at which stress circuits and endogenous opioid systems intersect and likely plays a critical role in the interaction between stress and drug addiction. Our prior studies demonstrate that the stress-related neuropeptide corticotropin-releasing factor (CRF) and the delta-opioid receptor (DOR) colocalize in interneuron populations in the hilus of the dentate gyrus and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 145 publications
(187 reference statements)
5
41
0
Order By: Relevance
“…We have demonstrated that CRHR1-IR is in dendritic spines of CA1 neurons (22), and E2 is involved is sex differences seen in stress-related changes in hippocampal-dependent behavior and cognition (48). Although GPR30 is associated with CRHR1 in vitro, the CRHR1-CT also contains a PDZ ligand sequence (-STAV) and can also co-immunoprecipitate with PSD-95.…”
Section: Gpr30 Interacts With the Dendritic Spine Scaffold Psd-95mentioning
confidence: 94%
See 2 more Smart Citations
“…We have demonstrated that CRHR1-IR is in dendritic spines of CA1 neurons (22), and E2 is involved is sex differences seen in stress-related changes in hippocampal-dependent behavior and cognition (48). Although GPR30 is associated with CRHR1 in vitro, the CRHR1-CT also contains a PDZ ligand sequence (-STAV) and can also co-immunoprecipitate with PSD-95.…”
Section: Gpr30 Interacts With the Dendritic Spine Scaffold Psd-95mentioning
confidence: 94%
“…All methods were approved by the Weill Medical College of Cornell University Institutional Animal Care and Use Committee (IACUC) as well as by The Rockefeller University IACUC and conform to the National Institutes of Health guidelines. Estrous cycle phases were determined as reported previously (22). Animals at both pro-and diestrus were used in the immunohistochemistry studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in the distribution of CRF receptors are also found in hippocampal CA1 dendrites [69]. In CA1, female rats have more CRF receptors in delta opioid receptor-containing dendrites than males [69]. These structural sex differences could lead to sex differences in interactions between CRF and endogenous opioids.…”
Section: Sex Differences In Crf Receptorsmentioning
confidence: 98%
“…In fact, this sex difference in CRF 1 receptor distribution is associated with increased anxiety in males following local administration of CRF into the DR [68]. Sex differences in the distribution of CRF receptors are also found in hippocampal CA1 dendrites [69]. In CA1, female rats have more CRF receptors in delta opioid receptor-containing dendrites than males [69].…”
Section: Sex Differences In Crf Receptorsmentioning
confidence: 98%